2020
DOI: 10.1111/tpj.15038
|View full text |Cite
|
Sign up to set email alerts
|

Structural determinants for NF‐Y subunit organization and NF‐Y/DNA association in plants

Abstract: SUMMARYNF‐Y transcription factor comprises three subunits: NF‐YA, NF‐YB and NF‐YC. NF‐YB and NF‐YC dimerize through their histone fold domain (HFD), which can bind DNA in a non‐sequence‐specific fashion while serving as a scaffold for NF‐YA trimerization. Upon trimerization, NF‐YA specifically recognizes the CCAAT box sequence on promoters and enhancers. In plants, each NF‐Y subunit is encoded by several genes giving rise to hundreds of potential heterotrimeric combinations. In addition, plant NF‐YBs and NF‐YC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 46 publications
1
32
0
Order By: Relevance
“…The results indicate that the numbers of NF-Y family members have increased in plants. Therefore, these NF-Y family genes may combine with each other to form tens of thousands of potential heterotrimers in plants [ 16 ]. The differentiation of the NF-Y family genes may lead to the diversity of their functions.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicate that the numbers of NF-Y family members have increased in plants. Therefore, these NF-Y family genes may combine with each other to form tens of thousands of potential heterotrimers in plants [ 16 ]. The differentiation of the NF-Y family genes may lead to the diversity of their functions.…”
Section: Introductionmentioning
confidence: 99%
“…Light is necessary to stabilize the CO protein, and numerous light-dependent molecular mechanisms involved in this process have been described [ 13 ]. CO protein plays a key role in the transcriptional activation of the florigens, forming a trimeric complex with NUCLEAR FACTOR-Y (NF-Y) B and C subunits at CONSTANS RESPONSIVE elements (CORE) located at the promoter of FT [ 17 , 18 ]. NF-Ys are highly conserved trimeric transcription factors (TFs) formed by NF-YA, NF-YB, and NF-YC subunits involved in many developmental processes including flowering [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, MeNF‐YC15 was also selected for further analysis. Considering NF‐YA, NF‐YB and NF‐YC usually form NF‐YA–NF‐YB–NF‐YC complexed to activate plant defense responses (Chaves‐Sanjuan et al., 2021; He et al., 2019), the interactions between MeNF‐YC15, MeNF‐YAs and MeNF‐YBs were investigated by point‐to‐point yeast two‐hybrid assay. The results showed that MeNF‐YA2/YA4 and MeNF‐YB18 interacted with MeNF‐YC15 (Figure 4a).…”
Section: Resultsmentioning
confidence: 99%
“…Considering the essential role of MeLSD3 in oxidative stress responses, MeGST‐U37 and MeGST‐U39 were selected for further analysis. Promoter region analysis revealed that CCAAT motifs, the targets of plant NF‐Y transcription factors (Chaves‐Sanjuan et al., 2021; He et al., 2019), were enriched in the promoters of MeGST‐U37 and MeGST‐U39 . We then tested whether they are direct targets of MeNF‐YC15.…”
Section: Resultsmentioning
confidence: 99%